2023
DOI: 10.31083/j.rcm2403073
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Atrial Fibrillation

Abstract: Dietary habits, including alcohol consumption, are among the significant risk factors for the occurrence of atrial fibrillation (AF). The pathophysiological relationship between alcohol consumption and AF is complex and multifactorial. However, there is conflicting information about the impact of alcohol consumption (in various doses and types) on the risk of AF and AF-related outcomes. Alcohol consumption is significantly associated with AF in a gender-independent manner. The widespread belief that moderate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(159 reference statements)
0
2
0
Order By: Relevance
“…Drinking RW or WW appears to be potentially safer than beer or spirits [119,120]. The dose of RW also seems to be relevant in influencing the risk of arrhythmia [121]. Consumption of two or more RW drinks per day was associated with a small but statistically significant increased AF risk [122].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drinking RW or WW appears to be potentially safer than beer or spirits [119,120]. The dose of RW also seems to be relevant in influencing the risk of arrhythmia [121]. Consumption of two or more RW drinks per day was associated with a small but statistically significant increased AF risk [122].…”
Section: Discussionmentioning
confidence: 99%
“…There are no RCT that have evaluated the effect of RW on the risk of arrhythmia. Some cohort studies have suggested that RW, when consumed in moderation, may have a protective effect against atrial fibrillation [118], while others have found no significant effects or even potential harm [119][120][121]. A study published in the Journal of the American College of Cardiology [119] demonstrated a J-shaped relationship between total alcohol consumption and risk of AF in a population of middle-aged and older adults.…”
Section: Discussionmentioning
confidence: 99%